Popular religion in the Middle Ages Western Europe 1000 - 1300 - Brooke, Rosalind; Brooke, Christopher (London, UK Thames and Hudson, 1984)
Includes bibliographical references, index, plates and illustrations.
Keywords: Church history -- Middle Ages -- Western Europe